1994
DOI: 10.1164/ajrccm.150.4.7921442
|View full text |Cite
|
Sign up to set email alerts
|

Nasal polyp inflammation. Effect of topical nasal steroid.

Abstract: Topical nasal corticosteroid therapy produces clinical improvement in patients with nasal polyposis. To examine the mechanisms of steroid effect, we quantified the number of inflammatory cell types as well as the expression of relevant cell markers in nasal polyps from steroid treated patients (n = 11) and polyps from untreated patients (n = 10) judged to require polypectomy for symptomatic relief. We found that the majority of eosinophils in these tissues were in the stromal layers, and that the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 0 publications
3
33
0
3
Order By: Relevance
“…The nasal polyp is a paradigm to mimic airway inflammatory diseases, in as much as it consists essentially of an oedematous stroma with numerous inflammatory cells, including neutrophils and most commonly eosinophils, plasma cells, mast cells, lymphocytes, and macrophages (29,30) covered by a respiratory type epithelium with large areas of basal and mucous cell hyperplasia or even squamous cells metaplasia (12). In fact, neither RT/PCR analysis of CFTR mRNA nor immunodetection of CFTR protein allowed us to detect any striking differences in the non-CF and CF nasal polyps to identify the AF 508 homozygosity.…”
Section: Discussionmentioning
confidence: 99%
“…The nasal polyp is a paradigm to mimic airway inflammatory diseases, in as much as it consists essentially of an oedematous stroma with numerous inflammatory cells, including neutrophils and most commonly eosinophils, plasma cells, mast cells, lymphocytes, and macrophages (29,30) covered by a respiratory type epithelium with large areas of basal and mucous cell hyperplasia or even squamous cells metaplasia (12). In fact, neither RT/PCR analysis of CFTR mRNA nor immunodetection of CFTR protein allowed us to detect any striking differences in the non-CF and CF nasal polyps to identify the AF 508 homozygosity.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory changes are similar to those observed in the inflamed bronchial mucosa in asthma [2, 3, 4]and are characteristic of polyp tissue whether or not allergy is present. It has been observed that the density of eosinophils in nasal polyp tissues is much greater than in control inferior turbinate tissues and that three quarters of eosinophils in the tissue are activated, as indicated by immunohistochemistry positivity with the monoclonal antibody EG2 [5]. …”
Section: Introductionmentioning
confidence: 99%
“…CD34 is expressed most strongly on primitive hemopoietic cells, and is progressively lost as cells differentiate (Strauss et al, 1986). Airway inflammation in patients with asthma and nasal polyps is characterized by the increased presence of several cell types, including mast cells, lymphocytes, and, in particular, eosinophils (Kanai et al, 1994). The aim of this study was to determine the immunohistochemical and histopathological changes on the nasal mucosa after propineb application.…”
Section: Introductionmentioning
confidence: 99%